Modernizing the federal government : paying for performance - Montoya, Silvia (Occasional paper (Rand Corporation) ;, 2007)
In 2003, the Volcker Commission recommended that explicit pay-for-performance (PFP) systems be adopted more broadly throughout the federal government. In this occasional paper, the authors compare several proposals aimed at enhancing the role of such PFP schemes for federal civil servants, and examine the pros and cons of PFP schemes compared with seniority-based salary systems, as well as the proposals to change the General Schedule system.